Failure analysis of nozzle zone before valve of negative pressure chamber from main pipe coolant system in nuclear power plant. (December 2017) - Bai, Bing; Zhang, Changyi; Lou, Xiao; Lin, Yun; Lin, Hu; Tong, Zhenfeng; Zheng, Honglian; Yang, Wen
Abstract: Nozzle zone before valve of negative pressure chamber from main pipe coolant system in the secondary circuit of reactor is made of F316 stainless as usual. The butt weld between nozzle and socket in main pipe is the weakest part. If the rupture occurs, it will directly lead to the leakage of main system. One nuclear power plant finds a local penetration crack in the weld of nozzle zone, and it leads to leakage in the inspection. The length of crack is 23.6 mm, nearly 41.7% of the perimeter. In this work, crack morphology observation, composition analysis, metallographic structure observation and hardness measurement are done for the leak part. Analysing with the service environment and force condition, the inner wall of nozzle has a greater stress concentration. It easily leads to fatigue cracking near the fusion line area with poor welding, and the crack extends from inner wall to outer wall. The fatigue crack evolves to corrosion fatigue crack during the crack propagation, and the further advices for use are provided. Highlights: Fatigue crack near the fusion line area with poor welding, which extends from inner wall to outer wall. The crack tip will be corroded with the water medium. The fatigue crack evolves to corrosion fatigue crack during the crack propagation. Crack morphology observation, composition analysis, metallographic structure observation and hardness measurement are done for the leak part. The finite element simulation analysis is necessary for force analysis of the nozzle.